Prison as a solution? The principles of eco-feminism applied to the social reintegration of women detainees - Ferreira, Helena (2022)
The aim of this investigation, born within activism, is to present an alternative to the current prison services that requires radical transformations in society. In other words, it aims to replace the space currently occupied by prisons with new institutions that will work to expel the prison from our social and psychic landscape. This project focuses on organizations in open spaces that prioritize the social wellbeing of female detainees and their families: ecovillages. Besides contributing to the global motion towards a society of sustainable communities, ecovillages promote social reintegration and solve the issue of severe poverty amongst female inmates. These ecovillages, built from the remnants of abandoned villages, on the principles of ecofeminism, provide an opportunity for women to overcome unfavorable conditions and build better lives for themselves and their communities – while contributing to the construction of a fairer, more sustainable democratic society.